Lys-plasminogen stimulates vitronectin exposure on the platelet surface - Zhernossekov, D.D.; Roka-Moiia, Y.M.; Tykhomyrov, A.A.; Grinenko, T.V. (Вiopolymers and Cell, 2015)
Aim. To study the vitronectin exposure on the platelet surface in the presence of two forms of the plasminogen molecule: Lys- and Glu-plasminogens. Methods. Research was conducted on human platelets. Aggregometry was used to check the platelet vitality and cell response towards thrombin. To evaluate the influence of different plasminogen forms on the platelet vitronectin exposure we used the method of flow cytometry. Results. It was found that incubation of resting platelets with Lys-plasminogen increased the amount of vitronectin-positive cells, but did not affect significantly their fluorescent intensity. Thrombin stimulation led to an increase in both: the number of vitronectin-positive platelets and the signal of fluorescence at least by two times. The Lys-plasminogen adding to the suspension of washed platelets followed by the thrombin stimulation enhanced the vitronectin exposure on the platelet surface and increased the amount of vitronectin-positive cells as compared to the isolated thrombin stimulation. Glu-plasminogen had no effect on the vitronectin exposure in case of resting or stimulated platelets. Conclusions. Lys-plasminogen but not its Glu-form enhances the exposure of vitronectin on the platelet surface. We suggest that the binding of Lys-plasminogen to the surface platelet receptors may generate plasmin that leads to the activation of intracellular signaling cascade.